El FONPRODE y la rendición de cuentas en la política española de cooperación al desarrollo - Ayuso, Anna; Cascante, Kattya (Revista Española de Desarrollo y Cooperación, 2023)
FONPRODE is configured as a financial instrument that despite their very nature, insists on being compatible with the contribution to development. To that purpose it should be established verifiable specific mechanisms of accountability. Its multilateral approach and coexistence marked with similar instruments in other European cooperation, including the Commission, requires international frames that incorporate accountability for its dual role: credit activity and concessional lending. This chapter discusses how the agenda of aid effectiveness addresses accountability and what should be expected from the Spanish system in relation to this instrument.